GE_GERICHTE P/23757/2024 vom 10. Oktober 2025 - GE Cour de justice (2025)
RUPTURE DE BAN;ERREUR SUR LES FAITS(DROIT PÉNAL);PEINE PÉCUNIAIRE;FRAIS JUDICIAIRES;DÉFENSE D'OFFICE;FIXATION DE LA PEINE | CP.291; CP.13; CP.47; CP.34; CPP.428; CPP.135